A revolta de Xandoca: desafio à oligarquia monteiro no ES (1916) - Bou-Habib Filho, Namy Chequer (2007)
Research about political and military disputes among Espírito Santo colonels, under the 1916 State succession scenery. The local opposition was present, encouraged by the Federal Government challenging the Souza Monteiro oligarchs, consolidated as the most powerful in the Old Republic. Election frauds, typical of that Republican period resulted in double election winners in every municipality, two sets of Congresses and two State Governors, on top of two capital cities in the State of Espírito Santo. A request of federal intervention fired up a national discussion and the crisis conclusion disclosed the influence of the oligarchical factions from Minas Gerais over the ones in Espírito Santo. The theme emphasizes the main role played by the opposition leaders, specially Alexandre Calmon, whose nickname was taken by History to turn the Xandoca Rebellion as a famous case.